2010
DOI: 10.1073/pnas.1006687107
|View full text |Cite
|
Sign up to set email alerts
|

Structures of aminoacylase 3 in complex with acetylated substrates

Abstract: Trichloroethylene (TCE) is one of the most widespread environmental contaminants, which is metabolized to N-acetyl-S-1,2-dichlorovinyl-L-cysteine (NA-DCVC) before being excreted in the urine. Alternatively, NA-DCVC can be deacetylated by aminoacylase 3 (AA3), an enzyme that is highly expressed in the kidney, liver, and brain. NA-DCVC deacetylation initiates the transformation into toxic products that ultimately causes acute renal failure. AA3 inhibition is therefore a target of interest to prevent TCE induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 36 publications
3
19
0
Order By: Relevance
“…Aminoacylase 2 (also called aspartoacylase) functions in the deacetylation of N-acetyl-L-aspartate through a CP-like mechanism (20). This is in contrast to its close relative, aminoacylase 3, which preferentially deacetylates N-acetylated aromatic amino acids (37). Mutations in aminoacylase 2 cause Canavan disease, a fatal and progressive neurodegenerative disease, due to greatly elevated levels of N-acetyl-L-aspartate (38).…”
Section: Discussionmentioning
confidence: 99%
“…Aminoacylase 2 (also called aspartoacylase) functions in the deacetylation of N-acetyl-L-aspartate through a CP-like mechanism (20). This is in contrast to its close relative, aminoacylase 3, which preferentially deacetylates N-acetylated aromatic amino acids (37). Mutations in aminoacylase 2 cause Canavan disease, a fatal and progressive neurodegenerative disease, due to greatly elevated levels of N-acetyl-L-aspartate (38).…”
Section: Discussionmentioning
confidence: 99%
“…Ebselen is a seleno-compound that easy reacts with reactive oxygen species and other cellular components, for example cysteine residues in proteins. Mouse AA3 has a cysteine residue (Cys175) in proximity to the active site (Hsieh et al, 2010), which modification by ebselen may decrease catalytic activity via restriction of substrate access to the active site. This possibility was excluded from consideration because purified human AA3 that has a glycine residue instead of cysteine (Pushkin et al, 2004; Tsirulnikov et al, 2009) was inhibited by ebselen to the same extent as mouse AA3 (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Mouse and human AA3 were expressed in E. coli and purified as described (Tsirulnikov et al, 2009; Hsieh et al, 2010). Both purified enzymes were homogeneous by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and immunoblotting with MR-C1 and CH-4 antibodies (data not shown).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations